2019
DOI: 10.1002/gepi.22181
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of popular TDT‐generalizations for family‐based association analysis

Abstract: The transmission disequilibrium test (TDT) is the gold standard for testing the association between a genetic variant and disease in samples consisting of affected individuals and their parents. In practice, more complex pedigree structures, that is siblings with no parents, or three‐generational pedigrees with possibly missing genotypes, are common. There are several generalizations of the TDT that are suitable for use with arbitrary pedigree structures. We consider three such frequently used generalizations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…We do not assess any indirect effects (e.g., maternal effect, parent-of-origin effect, imprinting) or any interaction effect (e.g., maternal-fetal genotype interactions, gene-environment interaction, epistasis) [Ainsworth et al, 2011]. We use the TDT-like methods exclusively as association tests [Laird and Lange, 2006], and do not explore their type I error rates separately for the other possible null hypothesis scenarios under the original “no linkage or no association” composite null hypothesis [Laird and Lange, 2008, Hecker, Laird and Lange, 2019]. We do not consider monads [Fan et al, 2013] or any other pedigree structure [Chen, Manichaikul and Rich, 2009, Hecker, Laird and Lange, 2019].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We do not assess any indirect effects (e.g., maternal effect, parent-of-origin effect, imprinting) or any interaction effect (e.g., maternal-fetal genotype interactions, gene-environment interaction, epistasis) [Ainsworth et al, 2011]. We use the TDT-like methods exclusively as association tests [Laird and Lange, 2006], and do not explore their type I error rates separately for the other possible null hypothesis scenarios under the original “no linkage or no association” composite null hypothesis [Laird and Lange, 2008, Hecker, Laird and Lange, 2019]. We do not consider monads [Fan et al, 2013] or any other pedigree structure [Chen, Manichaikul and Rich, 2009, Hecker, Laird and Lange, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…We use the TDT-like methods exclusively as association tests [Laird and Lange, 2006], and do not explore their type I error rates separately for the other possible null hypothesis scenarios under the original “no linkage or no association” composite null hypothesis [Laird and Lange, 2008, Hecker, Laird and Lange, 2019]. We do not consider monads [Fan et al, 2013] or any other pedigree structure [Chen, Manichaikul and Rich, 2009, Hecker, Laird and Lange, 2019]. We explore three different mother-child pair designs and their corresponding trio designs; other hybrid designs are certainly possible [Vermeulen et al, 2009, Gjerdevik et al, 2020] but are beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted in Chen et al 26 , if there is no variant where all three observed genotypes (mother, father, offspring) are heterozygous, the phase information can be recaptured from the observed unphased genotype data. However, as described in Hecker et al 14 , treating inferred haplotypes as observed haplotypes can lead to misspecification. Nevertheless, more specifically, if there is no variant for which both parental genotypes are heterozygous, haplotypes can be phased, and the resulting conditional genotype distribution obtained by the FBAT haplotype algorithm equals the conditional distribution where we treat the haplotypes as observed. If we restrict the genetic data to rare variants, this is true for most nuclear families.…”
mentioning
confidence: 99%